Sports talent identification and selection in Korea - Ko, B.-G. (Asian Conference on sport science. Sport science and elite training programme for world class performance. 25-26 October 2013. Hong Kong Sports Institute, Hong Kong, China, 2013)
The purpose of this study was to review how Korea Institute of Sport Science (KISS) had carried out sports talent identification and selection for enhancing athletic performance over the last three decades. In the 1980s, KISS had to prepare a sports talent identification program for the 1986 Asian Games and the 1988 Olympic Games. So, KISS developed test items for sports talent identification for various sports and had identified 4,359 talented adolescents in 30 sport events. Moreover, KISS developed the standards for elite athlete and had selected talented athletes using them. In the 1990s after the two big sports events, KISS established a Talented Athlete Selection Center and constructed the foundation of elite athlete recruitment system. In the 2000s, Korea had suffered a lot of difficulties in recruiting young athletes because of the government`s birth control policy effect and economic affluence. So, KISS developed an innovative sports talent identification program and had searched about 500 talented children every year. And KISS developed a new talented athlete selection program and had selected 1,682 talented athletes during 2000s. These new sports talent identification and selection programs are effective until now and would be the best resources to recruit elite athletes in Korea in the future as well.